Mean curvature flow of certain kind of isoparametric foliations on non-compact symmetric spaces - Koike, Naoyuki (CUBO, A Mathematical Journal, 2019)
In this paper, we investigate the mean curvature flows starting from all leaves of the isoparametric foliation given by a certain kind of solvable group action on a symmetric space of non-compact type. We prove that the mean curvature flow starting from each non-minimal leaf of the foliation exists in infinite time, if the foliation admits no minimal leaf, then the flow asymptotes the self-similar flow starting from another leaf, and if the foliation admits a minimal leaf (in this case, it is shown that there exists the only one minimal leaf), then the flow converges to the minimal leaf of the foliation in Câˆž-topology. These results give the geometric information between the leaves.